Experimental and simulation-based investigations of marine diesel engine performance against static back pressure. (15th October 2017) - Sapra, Harsh; Godjevac, Milinko; Visser, Klaas; Stapersma, Douwe; Dijkstra, Chris
Highlights: Combination of experiments and MVEM to study effects of back pressure on marine engine performance. Method applying smoke limit and thermal overload to define ceiling of acceptable back pressures. Two different turbocharging technologies and valve overlaps to tackle 1 mWC of back pressure. Abstract: After-treatment technologies are adopted in automobiles and ships to meet strict emission regulations, which increase exhaust back pressure. Furthermore, underwater exhaust systems are employed on board ships to save space, and reduce noise and pollution on working decks. However, water at exhaust outlet creates a flow resistance for the exhaust gases, which adds to the back pressure. High back pressure reduces the operating limits of an engine, increases fuel consumption, and can lead to exhaust smoke. While the effects of back pressure were recognized earlier, there is a lack of experimentally validated research on the performance limits of a turbocharged, marine diesel engine against high back pressure for the entire operating window. The focus of this research is to provide a comprehensive understanding of back pressure effects on marine diesel engine performance, and to identify limits of acceptable back pressure along with methods to tackle high back pressure. In this work, a pulse turbocharged, medium speed, diesel engine was tested at different loads and engine speeds; against different values of static back pressure. Additionally, mean value model simulations could be validated and were used to compare the performance of a pulse and constant pressure turbocharged engine against high back pressures of 1 meter water-column (mWC), and for two different values of valve overlap. Using the validated simulation model, the conceptual basis for the engine smoke limit as well as for thermal overloading is investigated. A methodology applying the conceptual basis to define boundaries of acceptable back pressures has been presented in this paper. A combination of pulse turbocharger systems and small valve overlap showed to significantly improve back pressure handling capabilities of engines.